Postulational Approach to Analytico-Synthetic Classification - Gopinath, M. A. (Journal of Information and Knowledge, 1985)
Presents the postulational framework of S R Ranganathan. Illustrate these postulates with examples of analysis of compound subjects in the field of agriculture. Correlates these postulates to the Absolute Syntax of S R Ranganathan.